The Influence of Transformational Leadership and Organizational Culture on Employee Performance with Organizational Commitment as a Mediating Variable - I Wayan Oka Putra Suartama; I Gede Cahyadi Putra; Ni Made Dwi Puspitawati; I Nengah Suardhika (Asia Pacific Journal of Management and Education (APJME), 2024)
Using organizational commitment as a mediating variable, this study looks at how transformational leadership and organizational culture affect worker performance at the Ministry of Law and Human Rights' Bali Regional Office. Utilizing SEM-PLS 3.0 for data analysis, the study included 169 employees with a sample size of 168. The findings indicated that organizational culture had a positive and significant impact on employee performance, while transformational leadership had no discernible effect. Furthermore, organizational culture and transformational leadership both improved organizational commitment, which in turn improved performance. The impact of organizational culture on employee performance was partially mediated by organizational commitment, while the effect of transformational leadership was fully mediated by it. These results suggest that since a positive organizational culture directly improves performance, enhancing it may be necessary to improve employee performance at the Bali Regional Office. Despite not having a direct impact on performance, transformational leadership is essential for increasing organizational commitment, which eventually improves worker performance. Therefore, initiatives to improve commitment and culture may be important tactics for improving employee results.